WHEAT YIELD IN MAGNETIC ANOMALIES AND BEYOND THEM - Lyushvin P.B. (IJRDO-Journal of Applied Science, 2020)
Ambiguous, sometimes contradictory conclusions follow from literary sources related to magnetic fields effects on wheat yield. There are statements on positive effect of short-term magnetic field increase on root system development, statements on close direct (sometimes reverse) yield dependence on natural changes in the magnetic field by hundredth-thousandths of per cents. Yield decline in areas of significant positive magnetic anomalies, for example, in Kursk magnetic anomaly (KMA), is explained by open ore mining which led to a drop in groundwater levels by tens to hundreds meters. To assess impact of significant anomalies on yield, we analyzed regions not so prone to anthropogenic declines in groundwater levels – Bryansk, Kaluga and Orel regions, north-east parts of Kharkiv and Odessa regions with the surrounding area. It was found out that complex effect of magnetic fields (on ionization, crystallization processes, loss of ferrous compounds from solutions) causes everywhere yield declines by several times compared to neighboring areas outside of magnetic anomalies. And this is despite similarity of soil condition, orography, precipitation and agricultural efforts. Available materials on soil moisture and Normalised Difference Vegetation Index (NDVI) were analyzed to define the effect causes and genesis. It was found out that, in spring, soil in areas with anomaly is as moistened as in the neighboring areas, but NDVI pictures for anomalies are "more green" (positive effect of the magnetic field on root system development). On the contrary, by middle – end of summer, low soil moisture and gray NDVI, and also yield declines are observed. For irrigated fields, yields are much higher everywhere.